Monitoring Tools of Water Temperature and pH in Fresh Water Fish Pool Based on the Internet of Things (IoT) - Amin, Muhammad; Ma'arif, Alfian; Suwarno, Iswanto (Signal and Image Processing Letters, 2022)
One of the fish species that can live in high salinity (euryhaline) is tilapia (Oreochromis niloticus). It is not surprising that tilapia can be found in brackish water, swamps, reservoirs, lakes and rivers. The growth rate of tilapia is influenced by age and water quality as well as the quality and quantity of feed given. The definition of growth is the increase in weight and also the length of the body of living things during a certain period of time. These parameters should be monitored for the survival of the fish. The use of Internet of Things (IoT) can be used as a monitoring and automation system for fish environmental parameters. IoT in this research was chosen because this system can simplify human work. The instruments needed in designing the monitoring system include components that function as the main controller, namely the Node MCU ESP2866 microcontroller, components for detecting water pH levels, namely a pH meter sensor type pH-4502C, and a water temperature measuring component, namely DS18B20. NodeMCU is the main component as a microcontroller as well as a component that connects to Wi-Fi. This system displays the temperature and pH of the water on the LCD and is sent to the android application. The results of the design of the temperature and pH monitoring tool obtained the average error value on temperature readings is 0.88%. The small error value gives the conclusion that the temperature sensor readings in this study are accurate. The pH acidity reading has an average error value of 0.42%. The small error value gives the conclusion that the pH sensor readings in this study are accurate. With the results of sensor value readings and errors, it can be concluded that the tool can be used and can work properly.